Dynamic mechanical loading facilitated chondrogenic differentiation of rabbit BMSCs in collagen scaffolds. Issue 2 (4th February 2019) - Cao, Wanxu; Lin, Weimin; Cai, Hanxu; Chen, Yafang; Man, Yi; Liang, Jie; Wang, Qiguang; Sun, Yong; Fan, Yujiang; Zhang, Xingdong
Abstract: Mechanical signals have been played close attention to regulate chondrogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). In this study, dynamic mechanical loading simulation with natural frequencies and intensities were applied to the 3D cultured BMSCs–collagen scaffold constructs. We investigated the effects of dynamic mechanical loading on cell adhesion, uniform distribution, proliferation, secretion of extracellular matrix (ECM) and chondrogenic differentiation of BMSCs–collagen scaffold constructs. The results indicated that dynamic mechanical loading facilitated the BMSCs adhesion, uniform distribution, proliferation and secretion of ECM with a slight contraction, which significantly improved the mechanical strength of the BMSCs–collagen scaffold constructs for better mimicking the structure and function of a native cartilage. Gene expression results indicated that dynamic mechanical loading contributed to the chondrogenic differentiation of BMSCs with higher levels of AGG, COL2A1 and SOX9 genes, and prevented of hypertrophic process with lower levels of COL10A1, and reduced the possibility of fibrocartilage formation due to down-regulated COL1A2. In conclusion, this study emphasized the important role of dynamic mechanical loading on promoting BMSCs chondrogenic differentiation and maintaining the cartilage phenotype for in vitro reconstruction of tissue-engineered cartilage, which provided an attractive prospect and a feasibility strategy for cartilage repair.